Investigation of corrosion inhibitory process of marine Vibrio neocaledonicus sp. bacterium for carbon steel. (November 2015) - Moradi, Masoumeh; Xiao, Tao; Song, Zhenlun
Highlights: The process of corrosion inhibitory effect of Vibrio neocaledonicus sp. was studied. The noticeable inhibitory effect was observed at first 45 min of exposure. Bacterial attachment and macromolecules adsorption induced the first inhibitory effect. The biofilm formation and maturation on the surfaces increased the inhibitory effect. A homogenous biofilm inhibited the diffusion of oxygen ions on the metal surfaces. Abstract: The present work explains the corrosion inhibitory process of Vibrio neocaledonicus sp. bacterium for carbon steel. The first and significant inhibitory effect was obtained after 45 min of exposing carbon steel in the bacterial solution due to the adsorption of organic macromolecules on the surfaces and decrease in dissolved oxygen concentration. After that, biofilm covered the surfaces homogenously and thickened by exposure time; so the corrosion inhibitory effect increased by exposure time. EDS results detected the oxygen amount decreased in the presence of bacterium by expousre time due to biofilm formation and hindering the oxygen diffusion on the metal surfaces.